Quality Management Platform in Research Institutes (Part 1) - Klembalska Agnieszka (Marketing of Scientific and Research Organizations, 2017)
Research institutes face a chance to take the lead in the system of commercialization of the effects of R&D. For the purpose it is necessary to strengthen their position in the market i.a. by reorganizing structures and focusing on quality management. A multi-faceted approach to the problem of quality in the activities of research institutes based on an analysis of stakeholders and products, led to the idea of creating a platform for quality management - an entity bringing together 3 sections: